Implementation of the KLT (Kejar Lancar Tahfidz) Method as a Strategy to Achieve Al-Qur'an Memorization Targets for Students at Ma'had 'Aly PPTQ Ibnu Abbas Klaten - Deki Ridho Adi Anggara; Moya Naila Halim (Tilawah: Journal of Al-Qur'an Studies, 2026)
This research is motivated by the issue of low memorization achievement among the students of Ma’had ‘Aly PPTQ Ibnu Abbas Klaten, where most of them have not reached the target of memorizing five juz each semester. Challenges such as lack of focus, low motivation, weak muraja’ah systems, and discomfort during memorization submission also affect the quality of their memorization. These conditions encouraged the institution to implement the KLT (Kejar Lancar Tahfidz) method as a strategy to improve the students’ memorization progress and quality. The purpose of this study is to describe the implementation of the KLT (Kejar Lancar Tahfidz) method in memorizing the Qur’an at Ma’had ‘Aly PPTQ Ibnu Abbas Klaten and to identify the supporting and inhibiting factors in its application. This research also aims to determine the extent to which the KLT method contributes to improving the students’ Qur’an memorization quality. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Primary data were obtained from the Head of Ma’had ‘Aly, tahfidz instructors, and students participating in the KLT program. Data analysis was carried out through data reduction, data presentation, and conclusion drawing and verification. Source triangulation was used to ensure data validity. The findings show that the KLT (Kejar Lancar Tahfidz) method is implemented through stages such as target setting, intensive tahfidz schedules, supervision by muhafidzah, memorization evaluation programs, and a system for mapping student progress. This method has proven effective in improving memorization quality, increasing motivation, and strengthening the discipline of muraja’ah among the students. Supporting factors include institutional commitment, intensive mentoring, and the supportive environment of the pesantren. Meanwhile, inhibiting factors include students’ psychological conditions, time management challenges, and differences in individual memorization abilities. Based on the research results, it is recommended that the KLT program continue to be developed by increasing the variety of memorization methods, strengthening students’ time management, and optimizing motivational guidance. The institution is also advised to enhance its periodic evaluation system and provide additional support for students with slower memorization abilities. Future research may focus on examining the relationship between the KLT method and the psychological aspects of Qur’an memorizers.